EFEKTIVITAS PENERAPAN TELEMEDICINE DI RUMAH SAKIT PADA MASA PANDEMI COVID-19: A SCOPING REVIEW - Indah Pusvitasari; Dumilah Ayuningtyas (Jurnal Darma Agung, 2022)
Since the establishment of COVID-19 on March 11 2020 as a world pandemic, various health service efforts have continued to be made, especially in terms of implementing telemedicine which is considered to be an alternative in preventing the spread of COVID-19 during a pandemic, considering that health services are at home pain must go on. Telemedicine is a combination of medical and information communication technology, which can provide health services without being limited by space. Since the COVID-19 pandemic, telemedicine has become one of the most popular choices in remote healthcare efforts, therefore the purpose of this systematic review is to discuss the effectiveness of implementing telemedicine during the COVID-19 pandemic targeting hospitals that have not yet implemented telemedicine considering the use of telemedicine. The research is a scoping review using the framework of Arskey and O'Malley. The implementation of telemedicine in hospitals has become quite attractive during the COVID-19 pandemic, but in practice, there are still obstacles such as the platforms and networks to be used, the level of accuracy of diagnosis, and regulations between hospitals.